Adipose tissue macrophages impair preadipocyte differentiation in humans. - Li Fen Liu; Colleen M Craig; Lorna L Tolentino; Okmi Choi; John Morton; Homero Rivas; Samuel W Cushman; Edgar G Engleman; Tracey McLaughlin (PLoS ONE)
Aim The physiologic mechanisms underlying the relationship between obesity and insulin resistance are not fully understood. Impaired adipocyte differentiation and localized inflammation characterize adipose tissue from obese, insulin-resistant humans. The directionality of this relationship is not known, however. The aim of the current study was to investigate whether adipose tissue inflammation is causally-related to impaired adipocyte differentiation. Methods Abdominal subcutaneous(SAT) and visceral(VAT) adipose tissue was obtained from 20 human participants undergoing bariatric surgery. Preadipocytes were isolated, and cultured in the presence or absence of CD14+ macrophages obtained from the same adipose tissue sample. Adipocyte differentiation was quantified after 14 days via immunofluorescence, Oil-Red O, and adipogenic gene expression. Cytokine secretion by mature adipocytes cultured with or without CD14+macrophages was quantified. Results Adipocyte differentiation was significantly lower in VAT than SAT by all measures (p<0.001). With macrophage removal, SAT preadipocyte differentiation increased significantly as measured by immunofluorescence and gene expression, whereas VAT preadipocyte differentiation was unchanged. Adipocyte-secreted proinflammatory cytokines were higher and adiponectin lower in media from VAT vs SAT: macrophage removal reduced inflammatory cytokine and increased adiponectin secretion from both SAT and VAT adipocytes. Differentiation of preadipocytes from SAT but not VAT correlated inversely with systemic insulin resistance. Conclusions The current results reveal that proinflammatory immune cells in human SAT are causally-related to impaired preadipocyte differentiation, which in turn is associated with systemic insulin resistance. In VAT, preadipocyte differentiation is poor even in the absence of tissue macrophages, pointing to inherent differences in fat storage potential between the two depots.